The use of ion mobility mass spectrometry to probe modulation of the structure of p53 and of MDM2 by small molecule inhibitors - Dickinson, Eleanor R.; Jurneczko, Ewa; Nicholson, Judith; Hupp, Ted; Zawacka-Pankau, Joanna; Selivanova, Galina; Barran, Perdita E. (Frontiers in Molecular Biosciences, 2015)
Developing drug-like molecules to inhibit the interactions formed by disordered proteins is sought after but challenging due in part to the lack of solved structures from conformationally dynamic systems. Ion Mobility Mass Spectrometry (IM-MS) is well positioned to assess protein ligand interactions along with the effect of a given inhibitor on conformation. Here we demonstrate the use of IM-MS to characterize the effect of two inhibitors RITA and Nutlin-3 on their respective binding partners: p53 and MDM2. RITA binds N-terminal transactivation domain of p53 (Np53) weakly, preventing direct observation of the complex in the gas phase. Nonetheless, upon incubation with RITA, we observe an alteration in the charge state distribution and in the conformational distributions adopted by Np53 in the gas phase. This finding supports the hypothesis that RITAs mode of action is via a conformational change in p53. Circular dichroism corroborates our gas phase findings, showing a slight increase in secondary structure content on ligand incubation, and HDX-MS experiments also highlight the dynamic properties of this protein. Using the same approach we present data to show the effect of Nutlin-3 binding to MDM2. MDM2 presents as two conformational families in the absence of Nutlin-3. Upon Nutlin-3 binding, the protein undergoes a compaction event similar to that exhibited by RITA on Np53. This multi-technique approach highlights the inherent disorder in these systems; and exemplifies the power of IM-MS as a technique to study transient interactions between small molecule inhibitors and oncogenic intrinsically disordered proteins.